Determination of Antibacterial, Anticancer, Catalytic, and Antioxidant Activities of Green Synthesized Silver Nanoparticles Derived from Alternanthera sessilis Leaf Extract - B. HariBabu; G. Vijaya Lakshmi (Research Advances in Microbiology and Biotechnology Vol. 5, 2023)
The present study evaluates the biogenesis of Ag NPs utilizing an aqueous extract of Alternanthera sessilis (Linn) leaf (A.S). Green nanotechnology is a novel field that employs green chemistry to generate nanoparticles Biological NP synthesis approaches provide up new opportunities for NP synthesis by utilizing natural reducing and stabilizing agents. It is a less expensive and more environmentally friendly alternative to chemical and physical procedures because it does not require any energy or toxic ingredients. The formation of Ag NPs was confirmed by UV-vis spectra analysis. The UV-visible spectrophotometer obtained a distinctive peak at 420 nm, the XRD validated the Crystalline FCC nature of biogenic Ag NPs, and the FTIR and Zeta-potential (±14) tests revealed that phyto-chemicals were responsible for Ag NP reduction and stabilization. TEM analysis revealed a spherical shape with a size of about 24 nm. According to FTIR and Zeta-potential examinations, the terpenoids and alkaloids in the aqueous extract of A.sessilis leaves acted as reducing and capping agents to stabilise the produced Ag NPs. Biogenic Ag NPs also displayed antioxidant, antibacterial, and catalytic activity against DPPH and ABTS+., two Gram positive and two Gram negative bacteria, and Various dyes (MB,Mo,CV,RhB,EY), respectively. The tests also revealed that Ag NPs were more effective against Gramme negative bacteria than Gramme positive bacteria in terms of antibacterial activity. Additionally, they demonstrated that Hela cells and the MCF-7 breast cancer cell line were resistant to the anticancer effects of Ag NPs. Stronger anticancer effects are produced at higher doses.